EFFECT OF OPERATING TEMPERATURE ON THE PERFORMANCE OF RELAXOR-FERROELECTRIC PLZT FILMS-BASED POWER ENERGY-STORAGE DEVICES - Thi Ha, Dang; Vu Cam Binh, Nguyen; Thi Toan Thu, Bui; Thi Luc, Nguyen; Thai Ha, Le (Journal of Forestry Science and Technology, 2023)
Thermal stability is a key factor to determine the applicability of dielectric capacitors in the power energy-storage devices. The effects of operating temperature on the polarization hysteresis, energy-storage performance, and charge-discharge cycling stability of thin-film capacitors have been revealed in this study by investigating the relaxor Pb0.92La0.08(Zr0.52Ti0.48)O3 (PLZT) thin film grown on Pt/Ti/SiO2/Si substrates using a sol-gel spin-coating technique. The PLZT thin films demonstrate good thermal stability of polarization hysteresis and outstanding energy storage properties over a wide temperature range from room temperature to 150°C. With increasing operating temperature up to 200°C, the polarization hysteresis loops gradually become more slanted and slightly broaden. The fluctuation in recoverable energy density is less than 8%, and the change of energy-storage efficiency is less than 12% at 200°C, which may be associated with the high dynamic polar nanoregions (PNRs) in relaxor ferroelectrics. At room temperature, PLZT thin film shows an excellent charge-discharge cycling life with fatigue-free performance after 1010 cycles in both discharge energy-storage density and energy-storage efficiency. However, the reduction of discharge energy-storage density and energy-storage efficiency, performed at an operating temperature of 200°C, is about 18% after 1010 charge-discharge cycles. All these results suggest that such PLZT thin film capacitors are very attractive for energy-storage applications operating under high-temperature conditions.